Relationship between Blood Pressure and Nutrition in Adolescents - D. Godia, Dr. Haresh; Nikam, Dr. Lalit H (International Journal of Innovative Research in Medical Science, 2018)
Aims and Objectives of study: This study was confined to healthy groups. Care was taken to exclude persons suffering from obvious disease and/ or recent history of illness Aims and Objective of present study are:- To find out BMI males and females To find out systolic and diastolic blood pressure in males and females. The various parameters which are studies are as follows:- Standing height in cms Weight in kgs. Resting pulse rate Resting systolic blood pressure in mm of Hg. Resting diastolic blood pressure in mm of Hg. Body Mass Index. Background - The study was conducted in GSMC medical college and Tertiary care Hospital. Total 100students were selected for study, out of 50 were male students and 50 were female students.